Image presented in online platform influence online friendship - Ades, Andaleep; Omar, Siti Zobidah; Adzharuddin, Nor Azura; Wan Abas, Wan Anita (Academe Research Journals, 2017)
An image usually defines one’s first impression. In fact, based on one’s first impression, a good image can be used as a basis for the formation of lasting relationships. On the online social platforms such as Facebook, images are important in online interactions as they enable an individual to garner attention from friends and other followers and to stimulate further interactions. Individuals tend to post images that are loveable and acceptable by their online friends. Therefore, the images posted on social media promote and nurture the online interactions for online friendship.